ANALISIS USAHA PENANGKAPAN UDANG REBON (Acetes sp) DENGAN ALAT TANGKAP SONDONG DI PESISIR GAMPONG PASAR ACEH KECAMATAN JOHAN PAHLAWAN KABUPATEN ACEH BARAT - Amarullah Amarullah (Universitas Teuku Umar, 2018)
Rebon is one of the results of kind crustaceans but with a very small size compared with other types of crustaceans. Because of its small size it is, these shrimp with shrimp called